Tubulointerstitial nephritis associated with ciprofloxacin intoxication - Cruzado Pizarro, Carlos (2025)
Ciprofloxacin, a commonly used antibiotic, can cause rare adverse effects such as acute tubulointerstitial nephritis, possibly associated with an immune-mediated reaction leading to interstitial inflammation and tubular damage. We present the case of an 18-year-old female patient, with no relevant medical history, who ingested 10 tablets of 500 mg ciprofloxacin in a single intake. She subsequently developed pelvic abdominal pain, nephritic syndrome, and acute kidney injury classified as AKIN stage 3. Urinalysis revealed >100 red blood cells per field and 1+ proteinuria; blood tests showed urea 157.7 mg/dL and creatinine 10.04 mg/dL. Kidney biopsy revealed tubulointerstitial nephritis with toxic tubular damage, a lymphomononuclear infiltrate with eosinophils, and mild fibrosis. She was treated with pulses of methylprednisolone, oral prednisone (0.5 mg/kg/day), and ranitidine, achieving full recovery: creatinine 1.1 mg/dL and resolution of microhematuria. This case highlights the importance of considering this rare complication in patients with acute kidney injury following fluoroquinolone use.